Global synchronization of dynamical networks with coupling time delays - Liu, B.; Teo, Kok; Liu, X. (Elsevier Science BV, 2007)
In this Letter, we aim to study global synchronization for dynamical network with multicoupling time delays. By utilizing the Lyapunov–Krasovskii functional method and linear matrix inequalities (LMIs), we derive some simple and efficient criteria in terms of LMIs for achieving global synchronization. Feedback controllers can be easily obtained by solving the derived LMIs. These feedback controllers can achieve global synchronization of the a closed-loop dynamical network with coupling time delays. Two examples and numerical simulations are solved so as to illustrate the results obtained.